Mediating Role of Organizational Cynicism in Relationship between Role Stressors and Turnover Intention: Evidence from Healthcare Sector of Pakistan - Tahira Nazir; Ungku Norulkamar Bt. Ungku Ahmad; Samina Nawab; Syed Fida Hussain Shah (International Review of Management and Marketing, 2016)
The study determines the consequent implications of role stressors over the turnover intentions of nurses in the subjected healthcare systems, while considering organizational cynicism as a mediator. The extant survey-based study was carried out based on path analysis, considered to validate a hypothetical causal model concluded upon the variables mentioned prior. Validity, of which was substantiated through the information accrued from 395 registered nurses of Rawalpindi and Islamabad; the twin cities of Pakistan. The study advocates of the directly proportionate relationship between the mentioned predicators and the resultant variable, in a significant manner, and too proposes the partially mediatory effect of organizational cynicism, when taken into consideration. Moreover, in particular what adds up to the distinctiveness of the present manuscript is the meagre amount of research carried out on uncivil practices and cynicism observed in nursing, which itself is one of the most overlooked professions in the developing country; Pakistan. The study in suggestive manner opts for inducing healthy work practices to ensure safer work environment for nurses to remain employed under, for longer tenures.